A model educational program for people with type 2 diabetes : A cooperative Latin American implementation study (PEDNID-LA) - Gagliardino, Juan José (2001)
Objective - To implement an educational program in 10 Latin American countries and to evaluate its effect on the clinical, biochemical, and therapeutic aspects as well as the economic cost of diabetes. Research design and methods - Educators from each participating country were previously trained to implement the educational model. The patient population included 446 individuals with type 2 diabetes; all patients were <65 years of age, did not require insulin for metabolic control, did not have severe complications of diabetes or life-limiting illnesses, and had not previously participated in diabetes education courses. Clinical and therapeutic data and the cost of their pharmacological treatment were collected 6 months before participation in the educational program (-6 months), on entry into the program (time 0), and at 4, 8, and 12 months after initiation of the program. Results - All parameters measured had improved significantly (P < 0.001) by 1 yearfasting blood glucose (mean ±SD) 10.6 ±3.5 vs. 8.7 ±3.0 mmol/l; HbA1c 9.0 ±2.0 vs. 7.8 ± 1.6%; body weight 84.6 ±14.7 vs. 81.2 ±15.2 kg; systolic blood pressure 149.6 ±33.6 vs. 142.9 ± 18.8 mmHg; total cholesterol 6.1 ±1.1 vs. 5.4 ±1.0 mmol/l; and triglycerides 2.7 ± 1.8 vs. 2.1 ±1.2 mmol/l. At 12 months, the decrease in pharmacotherapy required for control of diabetes, hypertension, and hyperlipidemia represented a 62% decrease in the annual cost of treatment ($107,939.99 vs. $41,106.30 [U.S.]). After deducting the additional cost of glucosuria monitoring ($30,604), there was still a 34% annual savings. Conclusions - The beneficial results of this educational model, implemented in 10 Latin American countries, reinforce the value of patient education as an essential part of diabetes care. They also suggest that an educational approach promoting healthy lifestyle habits and patient empowerment is an effective strategy with the potential to decrease the development of complications related to diabetes as well as the socioeconomic costs of the disease.